EgiCool - IoT Solution for Datacenter Environmental Control and Energy Consumption Monitoring - Gonçalves, V. (2025)
The increasing demand for digital services and cloud computing has brought the problem of energy consumption of datacenters and the quest for innovative solutions. Among the emerging approaches, free cooling stands out as a promising technique that allows a significant advancement in the operational efficiency of datacenters, contributing to environmental sustainability. The objective of this work is to detail the development of an IoT solution for monitoring the physical space of a datacenter, with the main purpose of evaluating solutions that led to a reduction in its energy consumption, through the implementation of free cooling. We intend to monitor the energy consumption, temperature and humidity inside and outside the datacenter. The data will be collected by sensors that are connected to ESP-32 microcontrollers, sent via Wi-Fi, using the MQTT protocol, to Amazon Web Service (AWS) IoT, stored in AWS DynamoDB, processed and presented in a web application. We concluded the first phase of development of the pro-posed IoT solution with the construction of a prototype and a feasibility study analysis.